Two zinc(II) coordination complexes based on an asymmetric multidentate ligand: syntheses, structures, selective fluorescence sensing of iron(III) ions and thermal analyses. Issue 1 (6th December 2017) - Liu, Yaru; Liu, Lan; Zhang, Xiao; Liang, Guorui; Gong, Xuebing
Abstract : Two new Zn II coordination complexes with the asymmetric multidentate ligand 1‐(1 H ‐benzotriazol‐1‐ylmethyl)‐2‐propyl‐1 H ‐imidazole have been synthesized and structurally characterized by single‐crystal X‐ray diffraction. The complexes were investigated by fluorescence and thermal analyses. Abstract : The rational selection of ligands is vitally important in the construction of coordination complexes. Two novel Zn II complexes, namely bis(acetato‐κ O )bis[1‐(1 H ‐benzotriazol‐1‐ylmethyl)‐2‐propyl‐1 H ‐imidazole‐κ N 3 ]zinc(II) monohydrate, [Zn(C13 H15 N5 )2 (C2 H3 O2 )2 ]·H2 O, (1 ), and bis(azido‐κ N 1 )bis[1‐(1 H ‐benzotriazol‐1‐ylmethyl)‐2‐propyl‐1 H ‐imidazole‐κ N 3 ]zinc(II), [Zn(C13 H15 N5 )2 (N3 )2 ], (2 ), constructed from the asymmetric multidentate imidazole ligand, have been synthesized under mild conditions and characterized by elemental analyses, IR spectroscopy and single‐crystal X‐ray diffraction analysis. Both complexes exhibit a three‐dimensional supramolecular network directed by different intermolecular interactions between discrete mononuclear units. The complexes were also investigated by fluorescence and thermal analyses. The experimental results show that (1 ) is a promising fluorescence sensor for detecting Fe 3+ ions and (2 ) is effective as an accelerator of the thermal decomposition of ammonium perchlorate.